Effects of BRL 38227 on potassium currents in smooth muscle cells isolated from rabbit portal vein and human mesenteric artery. - Russell, S. N. (1992)
1. Single smooth muscle cells were isolated from the rabbit portal vein and the human mesenteric artery and whole cell currents recorded at room temperature from either cell type by the whole cell voltage clamp technique. 2. In the rabbit portal vein cells addition of 10 microM BRL 38227 induced a quasi-instantaneous, voltage-insensitive and time-independent current which had a reversal potential of -75 mV under experimental conditions where the calculated EK was -83 mV. 3. Cells were held at 0 mV and BRL 38227 was added cumulatively to construct a dose-response relationship. BRL 38227 (0.03-10 microM) caused a dose-dependent outward shift in the holding current with an EC50 of 1.3 microM. 4. BRL 38227 (10 microM) had no effect on the delayed rectifier K+ current measured in the presence of 5 mM tetraethylammonium and no effect on the Ca(2+)-activated K+ current measured in the presence of 5 mM 4-aminopyridine. Similarly BRL 38227 had no effect on the Ca2+ current. 5. The BRL 38227-induced current was blocked by glibenclamide (10 microM) and phentolamine (100 microM), specific blockers of the ATP-sensitive K+ current in single cells. 6. In human isolated mesenteric artery cells, BRL 38227 (10 microM) induced a glibenclamide-sensitive current similar to, but smaller than, that observed in the rabbit portal vein. 7. We conclude that in these cells, BRL 38227 activates a potassium conductance which has the electrophysiological and pharmacological characteristics of ATP-sensitive K+ channels.